Research on reliability modeling of unmanned aircraft system avionics systems based on 5G - Qiang Zhou; Yongan Wei; Longjiang Zhu (International Journal of Distributed Sensor Networks)
With the development of technology, an unmanned aircraft system will play a significant role in Internet of things based on 5G. Avionics system is an important part of the unmanned aircraft system, and the reliability of the avionics system directly determines the ability to perform missions. This article deals with the problem of reliability modeling with unmanned aircraft system avionics systems built on Internet of things in the 5G scenario. First, based on the composition of the avionics system, the network structure of the unmanned aircraft system avionics system is presented. Then, to evaluate the reliability, a task model of the unmanned aircraft system avionics system is proposed. Finally, an illustration of unmanned aircraft system reliability performing reconnaissance is also presented. By analyzing the task performance, it is shown that redundancy design of the units can improve the reliability of the unmanned aircraft system avionics system.